The relationship between the PRE-DELIRIC score and the prognosis in COVID-19 ICU patients: The PRE-DELIRIC score in COVID-19 ICU - Taşdemir Mecit, Bilge Banu (Journal of Surgery and Medicine, 2023)
Background/Aim: The PRE-DELIRIC score is a test to detect delirium in the intensive care unit (ICU). Delirium has been studied as a factor associated with the clinical course of patients in COVID-19 intensive care. Our study aimed to investigate the relationship between the PRE-DELIRIC score and prognosis in patients followed in the COVID-19 ICU. Methods: Patients hospitalized in the COVID-19 ICU between March 2020 and May 2021 were retrospectively analyzed, and 461 patients were included in the study. The PRE-DELIRIC scores of the patients were calculated using data obtained from the hospital information system. Patients with a PRE-DELIRIC score ≥50 were considered Group 1, and those with a score <50 were considered Group 2. The groups were compared in terms of gender, Glasgow Coma Scale (GCS), Acute Physiology and Chronic Health Evaluation (APACHE II) score, Sequential Organ Failure Evaluation Score (SOFA), length of hospital stay, and mortality rates. Results: Of the 461 patients included in the study, 153 were female, and 308 were male. A high PRE-DELIRIC score was determined in 157 (34.1%) patients (Group 1), while 304 patients (65.9%) had lower scores (Group 2). The hospitalization duration was 9.6 (6.7) days, and the mortality rate was 87.2% in Group 1, compared to 8.2 (6.03) days and 38.1% in Group 2, respectively. A significant difference was observed in the length of hospital stay and mortality between the groups (P<0.001). The rate of patients who were intubated and followed up on an invasive mechanical ventilator (MV) was 81.5% in Group 1, whereas it was 16.4% in Group 2 (P<0.001). Conclusion: Our study found that patients with a high PRE-DELIRIC score indicating delirium had higher mortality rates and longer hospital and MV stays. Delirium is one of the factors affecting mortality in COVID-19 disease. We believe that the PRE-DELIRIC score, as one of these factors, can serve as an important prognostic test in COVID-19 ICU patients.